The Self-starring Perspective: The Player as a Character - Andrade, Fernando A.; Mota, Rosilane R. (Anais Estendidos do Simpósio Brasileiro de Jogos e Entretenimento Digital (SBGames), 2023)
This article explores and dissects five games that break the fourth wall in ways that are integral to the plot. It also tries to define and categorize them in order to develop a vocabulary that can aid in the discussion of the subverted concepts and mechanics and define some criteria for this subgenre proposed. Based on these criteria, the games were directly compared and their commonalities were extracted. Reactions to their unusual elements were also observed through playtests to better understand how these plots are structured and the effectiveness of this way of telling a story.